Tissue Distribution, Excretion, and Interaction With Human Serum Albumin of Total Bioflavonoid Extract From Selaginella doederleinii - Chen, Bing; Xu, Dafen; Li, Zhijun; Jing, Yafei; Lin, Luping; Li, Shaoguang; Huang, Liying; Huang, Xiuwang; Liu, Ailin; Lin, Xinhua; Yao, Hong (Frontiers in Pharmacology, 2022)
Selaginella doederleinii Hieron is a traditional Chinese medicinal herb widely used to treat different cancers. Previously, we showed that the total bioflavonoid extract of S. doederleinii (TBESD) exhibits anti-carcinogenic activities both in vitro and in vivo. However, the plasma protein binding and pharmacokinetics parameters of TBESD remain unclear. To investigate plasma protein binding, tissue distribution, and excretion of TBESD, rats were administered a single dose of TBESD (600 mg/kg) intragastrically and tissue distribution and excretion of TBESD components were determined by rapid high-performance liquid chromatography and tandem mass spectrometry. TBESD binding to human serum albumin (HSA) was assessed by fluorescence spectroscopy. TBESD components amentoflavone, delicaflavone, robustaflavone, 2″,3″-dihydro-3′,3‴-biapigenin, and 3′,3‴-binaringenin were rapidly absorbed and distributed in various tissues, mostly in the lungs, kidneys, and ovaries, without long-term accumulation. The excretion of bioflavonoids occurred mostly via the intestinal tract and constituted 30% of the administered dose up to 48 h. Spectral analysis indicated that TBESD had a dynamic quenching eﬀect on HSA by binding to one HSA site through hydrophobic interactions and hydrogen bond formation. This is the first comprehensive report on the tissue distribution, excretion, and plasma protein binding of TBESD. This study provides important information on TBESD pharmacokinetics necessary for its further development into a therapeutic form for clinical applications.